A Framework for Adapting Deep Brain Stimulation Using Parkinsonian State Estimates - Mohammed, Ameer; Bayford, Richard; Demosthenous, Andreas (Frontiers in Neuroscience, 2020)
The mechanisms underlying the beneficial effects of deep brain stimulation (DBS) for Parkinson’s disease (PD) remain poorly understood and are still under debate. This has hindered the development of adaptive DBS (aDBS). For further progress in aDBS, more insight into the dynamics of PD is needed, which can be obtained using machine learning models. This study presents an approach that uses generative and discriminative machine learning models to more accurately estimate the symptom severity of patients and adjust therapy accordingly. A support vector machine is used as the representative algorithm for discriminative machine learning models, and the Gaussian mixture model is used for the generative models. Therapy is effected using the state estimates obtained from the machine learning models together with a fuzzy controller in a critic-actor control approach. Both machine learning model configurations achieve PD suppression to desired state in 7 out of 9 cases; most of which settle in under two seconds.